Analisa dan Perancangan Sistem Informasi Company Profile pada PT. Ekatama Precast Indonesia - Ukri Arianto; Rizki Octavian; Samsul Bahri; Brigitha Agatha Rosidin; Aries Saifudin A.Md., S.T., M.Kom (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
A website is an important thing that must be owned by a company, especially companies engaged in the industrial sector, one of which is PT. Ekatama Precast Indonesia, which in this case still disseminates information and profiles of a company, still uses a manual method and is somewhat inefficient. In responding to the problems that occur, an analysis and an information system design that can be implemented include company profile information using the Software Development Life Cycle (SDLC) method. With the application of this method, a company profile website portal can be built so that the promotional media for PT. Ekatama Precast Indonesia which is carried out using a website can help companies to be more efficient and reach the wider community in carrying out promotions.